Studying of the effect of the genetic variant c.470T>C in the CHEK2 gene on increasing the risk of breast cancer in the population of the Russian Federation - E. I. Novikova; V. K. Bozhenko; E. A. Kudinova; V. A. Solodkiy (Успехи молекулярной онкологии)
Introduction. Currently, there are conflicting data regarding the effect of the c.470T> C germline mutation in the CHEK2 gene on increasing the risk of breast cancer (BC), so it is necessary to conduct research on large samples of patients, including in the Russian population, in order to analyze the contribution of this mutation to the risk of cancer developing.The aim of the study was to determine the frequency of occurrence of the genetic variant c.470Т>С in the CHEK2 gene in the Russian population in patients with BC and patients with benign breast diseases (BBD) to assess the possible effect of this deoxyribonucleic acid damage on the likelihood of cancer occurrence.Materials and methods. The study included 2,787 patients with BC and 1,004 patients with BBD who underwent examination and treatment at the Russian Scientific Center of Roentgenoradiology of the Ministry of the Russian Federation from 2010 to 2018. Molecular genetic study was carried out by real-time polymerase chain reaction to determine the characteristic of the Russian population hereditary genetic variant c.470Т>С in the CHEK2 gene using a diagnostic panel that allows to determine three germline mutations: c.1100delC, c.444+1G>A and c.470Т>С in the CHEK2 gene.Results. In patients with BC the frequency of the mutation c.470T>C in the CHEK2 gene was 3.8 %, in patients with BBD this mutation was detected in 4.7 % of cases. The frequency of the genetic variant c.470T>C in high-risk groups was: 5.1 % – for BC patients with clinical signs of hereditary disease and 4.9 % – for patients with BBD with a family history of cancer. There were no statistically significant differences between the frequency of the mutation c.470T>C in the general groups of BC patients and patients with BBD and the corresponding frequency in the high-risk groups, as well as in the groups of BC patients and patients with BBD (p >0.05).Conclusion. The results of this study indicate the probable absence of a relationship between the presence of the mutation c.470Т>С in the CHEK2 gene and an increased risk of BC.